Digital-Assisted Direct Reading Approach: Strengthening Student Engagement and Motivation in English Learning: Pendekatan Membaca Langsung Berbantuan Digital: Memperkuat Keterlibatan dan Motivasi Siswa Dalam Pembelajaran Bahasa Inggris - Muhria, Lanlan; Kurnihayati, Kurnihayati; Solihin, Rully Khoeru; Sundari, Fina Dewi (Journal of Society and Development, 2025)
Digital technology has significantly transformed the world of education. This includes English language learning, which still faces challenges due to student unmotivation and disengagement. The direct reading method has been proven effective in improving intensive and extensive reading skills, but if not combined with creative strategies, this method is often perceived as monotonous. Therefore, digital technology helps increase student motivation and engagement in reading and learning. This study employed a quasi-experimental method and a pretest-posttest control group design. Students selected through purposive sampling were 11th-grade students from a high school in Majalengka. Two classes served as samples. The experimental class, consisting of more than 35 students, used the digitally assisted direct reading method, while the control class used conventional methods. Research tools included reading comprehension tests, motivation questionnaires, observations, and semi-structured interviews. T-tests and effect sizes were used to analyze qualitative data; source triangulation was used for quantitative data. The results showed that the experimental group had significantly improved compared to the control group. The average reading comprehension score in the experimental group increased from 65.2 to 81.7, while in the control group, it increased from 64.8 to 72.4 (p = 0.001; d = 0.85). Student motivation in the experimental group increased from 3.21 to 4.12, while in the control group it only increased from 3.18 to 3.54. In the experimental group, student engagement in behavioral, emotional, and cognitive aspects increased significantly. Therefore, this study concludes that incorporating digital technology into the direct reading method is proven effective in improving student comprehension, increasing motivation, and engagement. Moreover, this is an appropriate approach to meet the learning needs of the modern generation.